SOCIALIZATION OF GADGET MONITORING IN CHILDREN - Detya Wiryany; Muhammad Arfan Humaedi; Niko Nur Maulana; Riyan Candra Muliawan; Shafira Aurenevia; Khansa Sabila (Universitas INABA, 2022)
Parent-child communication with a